2013
DOI: 10.1155/2013/139608
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Costs Associated with Ankylosing Spondylitis in Turkey: An Analysis from Nationwide Real-World Data

Abstract: Objectives. To explore health care costs associated with ankylosing spondylitis (AS) in Turkey. Methods. Research-identified data from a system that processes claims for all Turkish health insurance funds were analyzed. Adult prevalent and incident AS patients with two AS visits at least 60 days apart, identified between June 1, 2010 and December 31, 2010, with at least 1 year of continuous health plan enrollment for the baseline and follow-up years were included in the study. Pharmacy, outpatient, and inpatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
1
1
Order By: Relevance
“…However, in a previous study from Turkey by Ozin et al (20), AS rates were reported as 1% and 3.6% in UC and CD, respectively. These rates are nearly half the rates in our study, and presumably related with the geographic distribution of the patients, of whom 70% were from Middle Anatolia, in which the rate of AS is relatively lower than from western regions of Turkey (21).…”
Section: Discussioncontrasting
confidence: 44%
“…However, in a previous study from Turkey by Ozin et al (20), AS rates were reported as 1% and 3.6% in UC and CD, respectively. These rates are nearly half the rates in our study, and presumably related with the geographic distribution of the patients, of whom 70% were from Middle Anatolia, in which the rate of AS is relatively lower than from western regions of Turkey (21).…”
Section: Discussioncontrasting
confidence: 44%
“…Moreover, members of the Turkish Grand National Assembly and the Supreme Court as well as foreign insurance holders and some military personnel were excluded from the UHI Fund in the SSI. The data have been used in several outcomes research studies .…”
Section: Methodsmentioning
confidence: 99%